ANALYZING THE PRE-WRITING PROCESSES OF STUDENT-AUTHORED WRITINGS PUBLISHED IN MASS PRINT MEDIA - Mayke Melya Sari (Relawan Jurnal Indonesia, 2024)
This research was motivated by students writing published in mass print media. The researcher wants to find ways the students apply the pre-writing process in student publication in print media such as newspapers. This research is qualitative research with a case study method that aims to analyze and discover how the students apply the pre-writing process before publication. The researcher found two students had applied all the stages and one student had not fully applied all the stages in pre-writing. The stages that have been taken are choosing a topic and gathering ideas. Meanwhile, the steps that have not been applied are organizing ideas, defining a topic sentence, and outlining. The conclusion is the students applied all the stages and the students not fully apply the stages in pre-writing can both publish their writing in print media